High power dual-wavelength tunable fiber laser in linear and ring cavity configurations - Ahmad, Harith; Latif, Amirah Abdul; Zulkifli, Mohd Zamani; Awang, Noor Azura; Harun, Sulaiman Wadi (Optical Society of America, 2012)
We describe and compare the performances of two crucial configurations for a tunable dual-wavelength fiber laser, namely, the linear and ring configurations. The performances of these two cavities and the tunability in the dual-wavelength output varied from 0.8 to 11.9 nm are characterized. The ring cavity provides a better performance, achieving an average output power of 0.5 dBm, with a power fluctuation of only 1.1 dB and a signal-to-noise ratio (SNR) of 66 dB. Moreover, the ring cavity has minimal or no background amplified spontaneous emission (ASE).